Elon Musk and the quest for a fantastic future - Vance, Ashlee 1977- (Harper, an imprint of HarperCollinsPublishers, 2017)
This book spotlights the technology and vision of Elon Musk, the entrepreneur and innovator behind SpaceX, Tesla, and SolarCity, who sold one of his internet companies, PayPal, for $1.5 billion. Ashlee Vance captures the full spectacle and arc of the genius's life and work, from his tumultuous upbringing in South Africa and flight to the United States to his technical innovations and entrepreneurial pursuits. Vance uses Musks story to explore one of the pressing questions of our age: can the nation of inventors and creators who led the modern world for a century still compete in an age of fierce global competition? He argues that Musk is a contemporary amalgam of legendary inventors and industrialists including Thomas Edison, Henry Ford, Howard Hughes, and Steve Jobs
Keywords: Südafrika (Staat); USA; Musk, Elon / Juvenile literature; SpaceX (Firm) / Juvenile literature; Tesla Motors / Juvenile literature; PayPal (Firm) / Juvenile literature; Musk, Elon; PayPal (Firm); SpaceX (Firm); Tesla Motors; Businesspeople / United States / Biography / Juvenile literature; Businesspeople / South Africa / Biography / Juvenile literature; Businesspeople; South Africa; United States; Businesspeople / Biography; Biographies; Biography; Juvenile works; Biografie; Jugendbuch